KURSK STATE MEDICAL UNIVERSITY: PAST AND PRESENT - Viktor A. Lazarenko (Высшее образование в России, 2016)
Kursk state medical university celebrates its 80th anniversary in February 2015. Today it rapidly develops a large scientific and educational center and has a high rating among medical schools and universities in the country. The Kursk state medical university is recognized as a reliable business and social partner not only in Russia, but also in 50 countries of theworld. The article presents a brief history of the development of the University, as well as the current state of the educational process and scientific activity, illuminates aspects of management system and prospects of the University.